ANALYSIS OF THE RELATIONSHIP BETWEEN FINANCIAL MANAGEMENT IN THE INTERNAL FOUNDATION KHOIRU UMMAH CILACAP - Firdhaus, Faidzin; Ikhtiagung, Ganjar Ndaru; Hastuti, Hety Dwi (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2024)
As one type of non-profit entity, the Foundation has a mandate from the Law of the Republic of Indonesia to be able to manage its finances properly. This study was conducted related to the financial management relationship between Khoiru Ummah Cilacap Foundation and the business entities under it, which was carried out to find out the current management conditions, compare them with the ideal management principles, and provide a proposed road map for improving financial management. The research was conducted using descriptive qualitative methods by collecting data through interviews and observations, which will then be analyzed to obtain an overview of a problem. From the analysis of the data obtained, it is known that currently the financial management of the Foundation has not been fully integrated, so that it can be proposed to plan concrete steps for the integration of financial management so that the Foundation can optimize the liquidity and cash flow available for the sustainability of the Foundation's operations and all its business entities.